The truth about health care why reform is not working in America. - Mechanic, David, 1936- (New Brunswick, New Jersey Rutgers University Press, 2008)
n The Truth about Health Care, David Mechanic explains how health care in America has evolved in ways that favor a myriad of economic, professional, and political interests over those of patients. While money has always had a place in medical care, "big money" and the quest for profits has become dominant, making meaningful reforms difficult to achieve. Mechanic acknowledges that railing against these influences, which are here to stay, can achieve only so much. Instead, he asks whether it is possible to convert what is best about health care in America into a well functioning system that better serves the entire population. -BOOK JACKET.
Is reform possible?: the need for change and forces against it -- What is disease and what should we treat? -- Saving lives individually or in populations -- The murky challenge of mental health -- The activated patient and the doctors' dilemma -- The neglect of long-term care -- The quest for quality -- Setting fair limits -- Restoring trust in the health system -- The challenge of change -- Steps in our health future.
Includes bibliographical references (p. 189-210) and index.
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: Health care reform; Medical policy; Health Care Reform -- United States; Delivery of Health Care -- United States; Health Policy -- United States; Insurance, Health -- United States